Online mentoring for girls in secondary education to increase participation rates of women in STEM: A long-term follow-up study on later university major and career choices - Stoeger, Heidrun; Debatin, Tobias; Heilemann, Michael; Schirner, Sigrun; Ziegler, Albert (Annals of the New York Academy of Sciences, 2023)
An important first step in talent development in science, technology, engineering, and mathematics (STEM) is getting individuals excited about STEM. Females, in particular, are underrepresented in many STEM fields. Since girls' interest in STEM declines in adolescence, interventions should begin in secondary education at the latest. One appropriate intervention is (online) mentoring. Although its short-term effectiveness has been demonstrated for proximal outcomes during secondary education (e.g., positive changes in elective intentions in STEM), studies of the long-term effectiveness of STEM mentoring provided during secondary education-especially for real-life choices of university STEM majors and professions-are lacking. In our study, we examine females' real-life decisions about university majors and entering professions made years after they had participated in an online mentoring program (CyberMentor) during secondary education. The program's proximal positive influence on girls' elective intentions in STEM and certainty about career plans during secondary education had previously been demonstrated in several studies with pre-post-test waitlist control group designs. Specifically, we compared the choices that former mentees (n = 410) made about university majors and entering professions several years after program participation with (1) females of their age cohort and (2) females of a group of girls comparably interested in STEM who had signed up for the program but then not participated (n = 71). Further, we examined the explanatory contribution to these later career-path-relevant, real-life choices based on (1) mentees' baseline conditions prior to entering the program (e.g., elective intentions in STEM), (2) successful 1-year program participation, and (3) multiyear program participation. Findings indicate positive long-term effects of the program in all areas investigated.
CRIS-Team WoS Importer:2023-04-28